Recuperação de Informação Utilizando o Conceito de Folkauthority - Côgo, Filipe Roseiro; Silva, Sérgio R. Pereira da (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2010)
We describe the use of a social network called chain of authorities to improve the information retrieval in folksonomy-based systems. This social network is generated by using the Folkauthority concept, which describes the activity of granting cognitive authority to the information sources through the use of foksonomy. With the development of the proposed work it is expected to contribute to the improvement of information retrieval in folksonomy-based systems as well as to enrich the discussion on the area of Social Information Retrieval.